Phenols Catalyzed Biginelli Reactions: A Self Catalyzed Monastrol Protocol - Ghafoor, Abdul; Sajid, Naveed; Mukhtar, Asma; Ali, Shahid; Aslam, Samina; Noureen Shahi, Mahrzadi; Adnan, Muhammad; Ain Khan, Misbahul (Asian Journal of Chemistry, 2015)
A simple and efficient approach towards one step synthesis of various dihydropyrimidones and thiones (Biginelli reaction) was developed by using phenols as catalysts. The multicomponent reaction was conducted between aromatic aldehydes, active methylenes and urea (or thiourea) in an appropriate solvent. This seems to be a first example, where weak acids such as phenols have been employed with success.